Systematic Literature Review: Smart City Framework - Riki Riki; Setyawan Widyarto; Saliyah Kahar (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2021)
Smart cities are currently becoming the trend of large cities in the world and large cities in Indonesia. As the center of human civilization, cities cannot do without the problems of excess capacity and comfort. More and more people are migrating from the countryside to the cities, which brings new problems to the cities. Cities need to change to survive in the future. Strong indicators are needed to support cities, whether in terms of natural environment, society, communities, infrastructure, and education. In this article, we discuss a systematic literature review of research related to smart cities. The systematic literature review is divided into three stages, introduction stage, demographic analysis stage and result analysis. The results reveal important indicators of smart cities based on the conclusions of previous research